2011
DOI: 10.3892/ol.2011.518
|View full text |Cite
|
Sign up to set email alerts
|

Primary paratesticular osteosarcoma: A case report

Abstract: Abstract. Extraosseous osteosarcoma originating from paratesticular soft tissue is an extremely rare type of malignant tumor. With the exception of the present study, only one other case of osteosarcoma originating from paratesticular soft tissue has previously been reported. A 52-year-old man presented with a painless scrotal swelling and palpable mass. The patient underwent left orchiectomy with the diagnosis of testicular tumor. Pathological examination was suggestive of osteosarcoma without any different h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Testicular osteosarcomas have been reported in paratesticular and intratesticular locations, both of which are rare [2,[6][7][8]. They usually present with scrotal swelling with or without pain as was seen in this patient.…”
Section: Discussionmentioning
confidence: 97%
“…Testicular osteosarcomas have been reported in paratesticular and intratesticular locations, both of which are rare [2,[6][7][8]. They usually present with scrotal swelling with or without pain as was seen in this patient.…”
Section: Discussionmentioning
confidence: 97%
“…Although observed in previously published reports, these unique imaging finding have not been not emphasised. [4][5][6][7][8] Calcification may occur in other testicular tumors such as nonseminomatous germ cell tumors, particularly teratomas, and nongerm cell tumors such as large-cell calcifying Sertoli cell tumor. However, this is usually focal and/or heterogenous and not as pronounced as seen in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Hong R, et al[3] reported a 78-year-old man who had presented with a right hemi-scrotal swelling. He had ultrasound scan of scrotal contents which showed a hydrocele and a heterogeneous solid mass with focal calcification in his right testis.…”
mentioning
confidence: 99%
“…He remained well without any evidence of local recurrence or metastasis at his 44-month post-operative follow-up. Hong R, et al[3] stated the following:…”
mentioning
confidence: 99%